2018
DOI: 10.1111/zsc.12330
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of the Eocene whiptail stingrays (Myliobatiformes, Dasyatidae) of the Bolca Lagerstätte, Italy

Abstract: The Eocene whiptail stingrays of the family Dasyatidae from the Bolca Lagerstätte, NE Italy, are revised herein in detail. The analysis of the anatomical and morphometric features allows us to identify the species “Dasyatis” zigni (Molin, 1861) as a junior synonym of “D.” muricatus (Volta, 1796), and to assign it to the new genus Tethytrygon gen. n. This new taxon exhibits a unique combination of features (e.g., rhombic disc wider than long, elongated tail folds fail to reach the tip of the tail, thorns absent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 52 publications
3
23
1
Order By: Relevance
“…8). The tree recovered is similar to the ones depicted by Marramà et al [32, 36] including an improved resolution of the positions of Plesiobatis as well as of the Eocene freshwater stingrays Asterotrygon and Heliobatis . The monophyly of the Myliobatiformes, as recognized by McEachran et al [4], Carvalho et al [3], McEachran and Aschliman [63], and Aschliman et al [5] is confirmed and strongly supported herein (Bremer value 9) by ten synapomorphies.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…8). The tree recovered is similar to the ones depicted by Marramà et al [32, 36] including an improved resolution of the positions of Plesiobatis as well as of the Eocene freshwater stingrays Asterotrygon and Heliobatis . The monophyly of the Myliobatiformes, as recognized by McEachran et al [4], Carvalho et al [3], McEachran and Aschliman [63], and Aschliman et al [5] is confirmed and strongly supported herein (Bremer value 9) by ten synapomorphies.…”
Section: Resultssupporting
confidence: 79%
“…The monophyly of the Myliobatiformes, as recognized by McEachran et al [4], Carvalho et al [3], McEachran and Aschliman [63], and Aschliman et al [5] is confirmed and strongly supported herein (Bremer value 9) by ten synapomorphies. The phylogeny also detected a dichotomy within myliobatiforms (excluding Hexatrygon ) as recovered by Marramà et al [32, 36] with two main clades that partially correspond to the superfamilies Myliobatoidea and Dasyatoidea. The nature of the dichotomy is possibly linked to the different calcifications of radial cartilages, body shapes and swimming modes detected in these two groups by Schaefer and Summers [40].…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“… 2016 , 2019 ; Marramà et al . 2018a , b , c , 2019a , b , c, d ;). These batoids are represented by electric rays (Torpediniformes), guitarfishes (Rhinopristiformes), stingrays (Myliobatiformes) and three batoid species that were historically assigned to the thornback ray genus Platyrhina Müller & Henle, 1838 : † P. bolcensis Heckel, 1851 , † P. egertoni (De Zigno, 1876 ) and † P. gigantea (Blainville, 1818).…”
Section: Introductionmentioning
confidence: 99%